Body, Relationship, Space: Dance Movement Therapy as an Intervention in Embodied Social Work With Parents and Their Children. Issue 2 (3rd April 2021) - Crooks, Anna; Mensinga, Jo
ABSTRACT: Dance Movement Therapy (DMT) is an evidenced-based practice where the body is central. While embodiment in Social Work is emerging as an area of interest and could benefit from incorporating key DMT principles into practice, DMT could also benefit from adopting a social justice agenda. Illustrated through the lens of attachment and the parent–child relationship, themes from DMT literature position the body, relationship, and space as key areas of embodied practice. The DMT principles, when approached as an act for social justice, can potentially affect social transformation, beginning with the first relationship. IMPLICATIONS: Dance movement therapy provides social workers with an evidenced-based intervention to address attachment issues through embodied relationship. Embodied approaches to early intervention can positively impact relationships and communities across the life span and intergenerationally.